INTEGRATING LOCAL WISDOM IN ISLAMIC RELIGIOUS EDUCATION TO FOSTER RELIGIOUS MODERATION: A CASE STUDY OF SMP 6 BAYAN, NORTH LOMBOK - Safitri, Febi Ayu; Rasidin, Rasidin (Edukasi Islami : Jurnal Pendidikan Islam, 2026)
Islamic Religious Education plays a pivotal role in shaping students' religious moderation, particularly in multicultural societies vulnerable to intolerance and extremism. Yet, the lack of culturally contextual approaches often limits its effectiveness. This study analyzes the implementation of local wisdom-based IRE and its contribution to developing religious moderation among students at SMP Negeri 6 Bayan, North Lombok. A qualitative case study was employed. Data were gathered through in-depth interviews, participatory observation, and documentation involving the school principal, Islamic Religious Education teachers, and students as purposively selected informants. Local cultural values including mutual cooperation, deliberation, and indigenous practices make Islamic Religious Education more contextual and meaningful, effectively cultivating tolerant and inclusive attitudes among students. Local wisdom-based Islamic Religious Education significantly shapes students' religious moderation character and offers a replicable model for multicultural Islamic education reform, with implications for broader educational policy and practice.